Baicalin Induces Apoptosis of Gallbladder Carcinoma Cells in vitro via a Mitochondrial-Mediated Pathway and Suppresses Tumor Growth in vivo - Shu, Yi-Jun; Bao, Run-Fa; Wu, Xiang-Song; Weng, Hao; Ding, Qian; Cao, Yang; Li, Mao-Lan; Mu, Jia-Sheng; Wu, Wen-Guang; Ding, Qi-Chen; Liu, Tian-Yu; Jiang, Lin; et al. (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Baicalin, the main active ingredient in the Scutellaria baicalensis (SB), is prescribed for the treatment of various inflammatory diseases and tumors in clinics in China. In the present study, we evaluated the antitumor activity of baicalin for gallbladder carcinoma and the underlying mechanisms both in vitro and in vivo. Our results indicate that baicalin induced potent growth inhibition, cell cycle arrest, apoptosis and colony-formation inhibition in a dose-dependent manner in vitro. We observed inhibition of NF-κB nuclear translocation, up-regulation of Bax and down-regulation of Bcl-2, as well as increased caspase-3 and caspase-9 expression after baicalin treatment in vitro and in vivo, which indicates that the mitochondrial pathway was involved in baicalin-induced apoptosis. In addition, daily intraperitoneally injection of baicalin (15, 30 and 60 mg/kg) for 21 days significantly inhibited the growth of NOZ cells xenografts in nude mice, which improved the survival of baicalin-treated mice. In summary, baicalin exhibited a significant anti-tumor effect by suppressing cell proliferation, promoting apoptosis, and inducing cell cycle arrest in vitro, and by suppressing tumor growth and improving survival in vivo, which suggested that baicalin represents a novel therapeutic option for gallbladder carcinoma.
Keywords: xenograft